Моделі оцінки економічного ефекту та ефективності експортно-імпортних операцій (на прикладі парфумерно-косметичних підприємств хімічної промисловості) - Кононенко, Я. В. (Видавництво Львівської політехніки, 2015)
Розглянуто різні методологічні підходи до визначення економічного ефекту та економічної ефективності експортних та імпортних операцій промислових підприємств, акцент зроблено на діяльності парфумерно-косметичних підприємств хімічної промисловості. Визначено відмінності між поняттями економічного ефекту та економічної ефективності. Прості адитивні моделі розрахунку економічного ефекту не є достатніми для оцінки загальної ефективності експортно-імпортної діяльності підприємств. Окреслено підходи до розроблення багатофакторних моделей оцінки економічної ефективності експортної та імпортної діяльності підприємства. The existing methodological approaches to evaluating the economic effect and efficiency of export-import activities of enterprises are analyzed and proposals for their improvement are provided. It is known that in the national economic science in evaluating the effectiveness of exportimport operations of enterprises there are dominating approaches based on the calculation of indicators that can be defined as the instantaneous rate, and the average economic effect of transactions. The instantaneous rate is the economic effect of each specific export or import transaction, and the averaged economic effect is the effect of export (import) transactions for a certain period of time. It is emphasized that it is simpler to use the methods of the average cost of access to foreign markets distributed by years and their taking into account in additive formulae of economic effects. It is possible, if the mechanism of financial planning (budgeting) of an export project is used, which involves budgeting project. Several determining factors or groups of factors have an impact on the obtained result. We can rank these factors or groups of factors according to their significance (impact on the result) as follows: market pricing factors; production costs factors; forex volatility; credit influence; tax and regulatory policy factors; transaction costs factors. It is concluded that the ability of enterprises to affect the factor of efficiency of export and import transactions differs. The company can consider such factors as systemic risks and duly respond to their dynamics, minimizing their possible negative impact. Thus, in case of foreign trade transactions, it can use a set of traditional (bank guarantee, letter of credit, bill of exchange) and non-traditional (futures, options, forward, swap) financial instruments of risks management (hedging). Namely, the company should use a strategy of minimizing risks. The problem is that the detailed classification of branches isn’t provided by the State Statistics Service and this does not allow singling out the researched perfume and cosmetics complex from the general composition of the industry, separating it from the branches that have specific domestic sources of raw materials, for example, that of coke chemistry. However, the available data indicate that domestic production of complex chemical components for the perfume and cosmetics complex are practically absent or very insignificant in the market. It has been found that simple, reliable and effective methods of evaluating the effectiveness of export-import transactions are required along with the additive models ofь export-import transactions direct economic effect calculation. They must take into account: 1) complex probable nature of the interaction of factors that determine it, 2) comprehensive connectivity of export-import transactions in the production activities of domestic enterprises, 3) a means of the the company’s system effectiveness evaluation; 4) the specificity of domestic enterprises. So, we think it impossible to create a single synthesizing factor that would allow to unambiguously evaluate, compare and position enterprises engaged in export-import activities
Models of evaluating economic effect and economic efficiency of export-import transactions (case-study: perfume and cosmetics enterpises of chemical industry)
Keywords: економічний ефект; економічна ефективність; експортно-імпортна діяльність; парфумерно-косметичні підприємства; economic effect; economic efficiency; export-import activity; perfumery and cosmetics company